Improved multi-layer wavelet transform and blind source separation based ECG artifacts removal algorithm from the sEMG signal: in the case of upper limbs - Lu, Wei; Gong, Dongliang; Xue, Xue; Gao, Lifu (Frontiers in Bioengineering and Biotechnology, 2024)
Surface electromyogram (sEMG) signals have been widely used in human upper limb force estimation and motion intention recognition. However, the electrocardiogram(ECG) artifact generated by the beating of the heart is a major factor that reduces the quality of the sEMG signal when recording the sEMG signal from the muscle close to the heart. sEMG signals contaminated by ECG artifacts are difficult to be understood correctly. The objective of this paper is to effectively remove ECG artifacts from sEMG signals by a novel method. sEMG and ECG signals of the biceps brachii, brachialis, and triceps muscle of the human upper limb will be collected respectively. In this paper, a novel ECG artifact removal method called IWT-FastICA algorithm is proposed based on wavelet decomposition theory and blind source separation theory. Firstly, an improved multi-layer wavelet transform (IWT) algorithm is used to preprocess the raw sEMG signal to remove the background noise and power frequency interference in the raw signal. Then, based on the theory of blind source separation analysis, an improved Fast-ICA algorithm was constructed to separate the denoising signals. Finally, an ECG discrimination algorithm was used to find and eliminate ECG signals in sEMG signals. This method consists of the following steps: (1) Acquisition of raw sEMG and ECG signals; (2) Decoupling the raw sEMG signal; (3) Fast-ICA-based signal component separation; (4) ECG artifact recognition and elimination. The experimental results show that our method has a good effect on removing ECG artifacts from contaminated sEMG signals. It can further improve the quality of sEMG signals, which is of great significance for improving the accuracy of force estimation and motion intention recognition tasks. Compared with other state-of-the-art methods, our method can also provide the guiding significance for other biological signals.